2012
DOI: 10.1002/jobm.201200152
|View full text |Cite
|
Sign up to set email alerts
|

A 2,3‐butanediol dehydrogenase from Paenibacillus polymyxaZJ‐9 for mainly producing R,R‐2,3‐butanediol: Purification, characterization and cloning

Abstract: A 2,3-butanediol dehydrogenase (BDH) from Paenibacillus polymyxa ZJ-9 was purified to homogeneity via fractional ammonium sulfate precipitation, followed by two steps of anion-exchange chromatography using DEAE-Sepharose and Source 15Q, obtaining a 35-fold increase in specific activity and 34.9% yield. The molecular weights of the purified BDH subunit and holoenzyme were 44.5 and 90.0 kDa, respectively, as detected via SDS-PAGE and gel filtration chromatography. These results were significantly different from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Characterization and gene cloning of 2,3‐BDO dehydrogenase by Paenibacillus polymyxa ZJ‐9 showed that this enzyme is a new type of BDH, significantly different than other reported BDHs. It acts more like a reductase of R ‐acetoin rather than a dehydrogenase 34. R ‐BDH from P. polymyxa ATCC 12321 was functionally characterized and classified in a medium‐chain dehydrogenase/reductase superfamily, differently from meso ‐ and S ‐BDH, which belong to the short‐chain dehydrogenase/reductase superfamily 35.…”
Section: Microbial Production Metabolismmentioning
confidence: 99%
“…Characterization and gene cloning of 2,3‐BDO dehydrogenase by Paenibacillus polymyxa ZJ‐9 showed that this enzyme is a new type of BDH, significantly different than other reported BDHs. It acts more like a reductase of R ‐acetoin rather than a dehydrogenase 34. R ‐BDH from P. polymyxa ATCC 12321 was functionally characterized and classified in a medium‐chain dehydrogenase/reductase superfamily, differently from meso ‐ and S ‐BDH, which belong to the short‐chain dehydrogenase/reductase superfamily 35.…”
Section: Microbial Production Metabolismmentioning
confidence: 99%
“…Because operational parameters vary for different environment‐medium‐microorganism, the optimal value should be established individually for each strain and substrate used. More recently, some studies have focused on the genetic modification of yeasts and bacteria toward the production of 2,3‐BD, but the reported results of productivity and yields of this chemical are often low when compared to values obtained using wild‐type strains …”
Section: Introductionmentioning
confidence: 99%
“…D -2,3-butanediol as one of the promising bulk chemicals has extensive applications in cosmetics, foods, transport fuels, medicines, and polymers industries [ 1 ]. In general, 2,3-butanediol exists in three stereoisomeric forms: D -2,3-butanediol, L -2,3-butanediol and meso -2,3-butanediol [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…All these isomers are valuable chemicals that provide chiral groups in drugs [ 3 ]. D- 2,3-butanediol is also used as an antifreeze agent because of its low freezing point (-60°C) [ 1 ]. The production of 2,3-butanediol with high optical purities is therefore highly desirable [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%